A critical appraisal of the premotor symptoms of Parkinson's disease: Potential usefulness in early diagnosis and design of neuroprotective trials - Lang, Anthony E. (Movement disorders, 2011)
The neurodegenerative process is well established in Parkinson patients presenting to a physician with early motor signs. There is increasing evidence that a variety of nonmotor features can antedate the typical presentation by many years. As the search for successful disease‐modifying treatment advances, it is logical to consider how this could be applied to patients in the earliest stages of the disease, indeed before motor features develop, with the obvious goal of delaying and even preventing the onset of the motor syndrome. However, many of these nonmotor symptoms are rather nonspecific and are not uncommon in the general population. Being able to identify individuals in whom these features are more likely to represent true premotor Parkinson's disease represents a major challenge. Until widely applicable and reliable biomarkers for the presence of Parkinson's disease‐related pathology are developed (including biomarkers of disease severity and rate of progression), further evaluation of possible premotor features in selected populations will probably serve as the basis for future studies of disease‐modifying therapies. This article will review the current status of premotor symptoms of Parkinson's disease and discuss their potential for early diagnosis and the design of neuroprotective trials. © 2011 Movement Disorder Society